Protein targeting protocols - Clegg, Roger A. (Methods in molecular biology, 1998)
In Protein Targeting Protocols, master experimentalists describe, largely from the perspective of intracellular signaling, their best time-tested methods for detecting and analyzing the proteins and protein motifs involved in cellular targeting interactions. The techniques range from basic methods that reveal the existence of targeting interactions and characterize physicochemical properties to those for analyzing the more structurally elaborate systems involved in the movement of molecules between cellular compartments, with examples taken from nuclear transport, clathrin-coated vesicle traffic, and secretory sorting. The themes of targeting domains, particularly the SH-2, SH-3, and PH domains, and the principal targeting of lipid modifications-myristoylation, reversible palmitoylation, prenylation-are fully explored. Protein Targeting Protocols offers a valuable collection of both basic and state-of-the-art techniques suitable for use in all areas of molecular cell biology by researchers interested in defining and characterizing the wide variety of protein interactions underlying targeting mechanisms. Readers will find it serves well as a firm methodological foundation for laboratories newly entering this field and as an indispensable reference work for those already well-established in it